Religious Attitudes and Radical Behavior of Islamic Boarding School Students - Sarbini Sarbini; Moh. Dulkiah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
Previous studies on radicalism among Islamic school students mostly focused on those residing in boarding schools. However, some students did not reside in the boarding school but usually participated in radicalism as